The extent to which science teachers at the intermediate stage apply creative thinking skills - Al-Thowaibi, Tahani Saad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the extent to which science teachers in the middle stage practice creative thinking skills, and to reveal the extent to which science teachers in the middle stage apply creative thinking skills (fluency, originality, flexibility), and to reveal statistically significant differences at the significance level (0.05) between the averages responses Science teachers at the intermediate stage in Taif for creative thinking skills due to the two variables (qualification, experience). To achieve the objectives of the study, the researcher used the descriptive approach, and the questionnaire was used as a study tool prepared by the researcher. In its final form, it consisted of (23) indicators distributed on three axes: (fluency, originality and flexibility). The validity and reliability of the tool were verified through the exploratory sample and then applied to the study sample. , where the community sample consisted of (210) science teachers in government schools in Taif, and the study sample consisted of (114) science teachers, and the study reached a set of results, the most important of which are:The extent to which science teachers at the intermediate stage in Taif apply creative thinking skills (flexibility) obtained a verification rate of (87.1%) with a grade (strongly agree) and an arithmetic mean of (4.4), and the extent to which science teachers at the intermediate stage in Taif apply creative thinking skills (Authenticity) obtained a verification rate of (84.7%) with a grade (strongly agree) and an arithmetic average of (4.2), and the extent to which science teachers at the intermediate stage in Taif apply creative thinking skills (fluency) obtained a verification rate of (84.6%). With a grade of (strongly agree) and an arithmetic mean of (4.2), and there are no statistically significant differences at the level (0.05) or less between the views of science teachers at the intermediate stage in Taif on the extent to which creative thinking skills are applied according to the two variables (qualification - number Years of Experience).
Keywords: creative thinking; science teachers; middle school